Fecal calprotectin for the prediction of small-bowel Crohn's disease by capsule endoscopy: a systematic review and meta-analysis. Issue 10 (October 2016) - Kopylov, Uri; Yung, Diana E.; Engel, Tal; Avni, Tomer; Battat, Robert; Ben-Horin, Shomron; Plevris, John N.; Eliakim, Rami; Koulaouzidis, Anastasios
Abstract : Background and aims: Fecal calprotectin is a well-established marker of mucosal inflammation. Although the correlation of elevated calprotectin levels with colonic inflammation has been confirmed repeatedly, it is less established for the small bowel. The aim of the current study was to assess the diagnostic accuracy of calprotectin for the prediction of active small-bowel disease on capsule endoscopy by performing a diagnostic test meta-analysis. Materials and methods: A comprehensive search was performed using PubMed/Embase. Studies addressing patients with suspected/established Crohn's disease (CD) evaluated with calprotectin and videocapsule were included. A diagnostic meta-analysis was carried out; pooled diagnostic sensitivity, specificity, and diagnostic odds ratio (DOR) were calculated for each cut-off. Results: Seven studies (463 patients) were entered into the final analysis. The DOR was significant for all the evaluated FC cut-offs (50 μg/g: sensitivity 0.83, specificity 0.53, DOR-5.64; 100 μg/g: sensitivity 0.68, specificity 0.71, DOR-5.01; 200 μg/g: sensitivity 0.42, specificity 0.94, DOR-13.64). On sensitivity analyses, when only studies addressing suspected Crohn's or retrospective studies were included, the results did not change significantly. For studies including patients with suspected CD only, the overall accuracy for FC cut-off 50 μg/g was further increased (sensitivity 0.89, specificity 0.55, DOR-10.3), with a negative predictive value of 91.8%. Summary and conclusion: Fecal calprotectin has a significant diagnostic accuracy for the detection of small-bowel CD. Our results suggest that in patients with suspected CD with calprotectin <50 μg/g, the likelihood of positive diagnosis is very low.